Hsp90β promoted endothelial cell-dependent tumor angiogenesis in hepatocellular carcinoma - Jing Meng (Molecular Cancer, 2017)
Abstract Background Vascular endothelial growth factor receptors (VEGFRs) are the major receptors involved in endothelial cell-dependent tumor angiogenesis. There are studies account for the effects of Hsp90 on angiogenesis, but the role and mechanism of Hsp90β isoforms and NVP-BEP800, a specific inhibitor of Hsp90β, in tumor angiogenesis is rarely mentioned. Methods Immunohistochemistry and statistical analysis was used to evaluate the correlation between Hsp90β expression, CD31 endothelial cell-dependent vessel density, and VEGFRs expression in tissue samples of 96 HCCs. Kaplan-Meier survival analysis and COX proportional hazards analysis the relation of Hsp90β and prognosis. HUVEC cells were transfected with Hsp90β or treated with NVP-BEP800, and then cell proliferation, migration, invasion and tube formation were investigated. The VEGFR1 and VEGFR2 expression was determined by Western blot and immunofluorescence. The VEGFR1 and VEGFR2 promoter activities were detected by dual luciferase report system. In vivo, the angiogenesis promotion of Hsp90β and anti-angiogenesis efficacy of NVP-BEP800 was tested in HCC xenograft models. Histological analysis was performed on tumor samples to evaluate Hsp90β, VEGFRs expression and MVD. Results This study investigated the correlation between Hsp90β expression and CD31+ endothelial cell-dependent vessel density. Hsp90β promoted VEGFRs expression by increasing their promoter activities. The proliferation, migration, invasion, and tube formation activities of human endothelial cells significantly increased when Hsp90β was overexpressed. NVP-BEP800 down-regulated VEGFRs expression to significantly reduce tubular differentiation, as well as endothelial cell proliferation, migration, and invasion. Furthermore, NVP-BEP800 decreased VEGFR1 and VEGFR2 promoter activities. In vivo, Hsp90β promoted VEGFRs and CD31 expression in human hepatocellular carcinoma tumor xenografts and was associated with increased tumor microvessel density. After 18 days of treatment with 30 mg/kg/day NVP-BEP800, VEGFRs and CD31 expression significantly decreased. Conclusion Hsp90β induced endothelial cell-dependent tumor angiogenesis by activating VEGFRs transcription. NVP-BEP800 has potential as a therapeutic strategy for inhibiting tumor angiogenesis by decreasing endothelial cell progression and metastasis. It can help develop a therapeutic strategy for tumor treatment through the inhibition of endothelial cell progression and metastasis.